Ritual Communication and Cultural Resilience in Digital Space: A Netnographic SPEAKING Model Analysis of Peresean in the Modernization Era - Ilmining Mandiri; Mite Setiansah; Wiwik Novianti (Jogjakarta Communication Conference (JCC), 2026)
Modernization and digitalization have transformed traditional rituals into digital content, raising questions about the continuity of their communicative structures. This study analyzes the transformation of the Peresean ritual on TikTok using a netnographic approach and Dell Hymes SPEAKING model. By examining 20 videos uploaded between 2024 and 2026, the study maps how ritual communication is reconfigured in digital space. The findings indicate that the elements of Setting, Participant, and Act Sequence undergo significant transformation: the ritual arena shifts from a physical community space to an algorithmic digital stage, participants expand to include active online audiences, and ritual sequences become fragmented due to short video formats. However, the elements of Norms and Key remain consistent, as sportsmanship values are reaffirmed through audience interaction in the comment section. The element of Genre also reveals variations in representation across account categories, including documentation, tourism promotion, and entertainment framing. These results demonstrate that digital modernization does not eliminate ritual meaning but reconfigures its communicative structure through symbolic adaptation and audience negotiation. The study contributes to ritual communication research by applying the SPEAKING model to analyze cultural resilience within the social media.